The increasing role of IT auditors in financial audit: risks and intelligent answers - Barta, Gergő (Business, Management and Economics Engineering, 2018)
Financial auditing cannot be imagined without the involvement of IT specialists since business processes are designed to be served by IT components such as ERP systems, online customer-facing applications, databases etc. Financial auditors therefore exposed to IT system and control reliance want to gain reasonable assurance that data and transactions stored in IT systems cannot be modified, access is controlled, and there is no suspicion of any fraud at business organizations. The paper tries to understand the current situation of IT audit involvement in financial auditing, interpret risks that parties face and provide some solutions by use of intelligent applications.